2015
DOI: 10.1111/ipd.12193
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life in 6‐ to 12‐year‐old schoolchildren in Spain

Abstract: Pain and aesthetic-related domains (i.e., problems when eating or smiling) are the major components of the oral health-related quality of life perceived by Spanish schoolchildren. Perceived treatment needs as well as dental and periodontal status were the strongest predictors of oral well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…For example, a report from Brazil showed impact on the oral health of 88.7% of schoolchildren ages 11 and 12, mainly experienced as chewing difficulties [46]. Furthermore, an association between eating problems and a negative impact on OHRQoL was detected in Spanish children ages 6 to 12 [47]. A rather innovative perspective was afforded by the GSEM analysis, which showed that tooth brushing was associated both directly with CPQ score, and also indirectly through caries and fluorosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a report from Brazil showed impact on the oral health of 88.7% of schoolchildren ages 11 and 12, mainly experienced as chewing difficulties [46]. Furthermore, an association between eating problems and a negative impact on OHRQoL was detected in Spanish children ages 6 to 12 [47]. A rather innovative perspective was afforded by the GSEM analysis, which showed that tooth brushing was associated both directly with CPQ score, and also indirectly through caries and fluorosis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this is the greater presence of dentobacterial plaque caused by intake of fried, high carbohydrate foods between regular meals. This in turn can directly affect teeth and gums exposed for long periods [34]. In conjunction with poor oral health practices, this could explain the greater possibility of dental pain in this group of children.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that dental caries can be asymptomatic, particularly at its initial stages, caries is associated with diminished quality of life for people affected and their families 128 . Among children, caries is associated with negative impacts on a range of daily life activities 129,130 and this was the case also among very young children where caries was associated with worse oral health related quality of life in terms of perceptions of both children and their parents 131 . Similarly, toothache and tooth decay are the conditions most commonly associated with worse oral health related quality of life on adults.…”
Section: [H1] Quality Of Lifementioning
confidence: 98%